HUBUNGAN PEMENUHAN KEBUTUHAN SPIRITUAL DENGAN KUALITAS HIDUP PASIEN GAGAL GINJAL KRONIS DI RUANG HEMODIALISA RSUD SANJIWANI - Ni Made Wida Prastini; Ni Luh Putu Dina Susanti; Asthadi Mahendra Bhandesa (Universitas Tabanan, 2023)
Background: Chronic kidney failure is a decrease of kidney function that occurs due to tissue damage in the kidney, which makes the patient have to undergo hemodialysis. However, a lifelong hemodialysis makes the quality life of the patients decrease, so one approach that can be taken is to provide emotional support. One of them is the fulfillment of spiritual needs. Purpose: To determine the correlation between fulfillment of spiritual needs and quality of life in patient with chronic kidney failure. Method: This study employed descriptive correlation design with cross-sectional approach. There were 130 respondents recruited as sample of the study which were selected by using total sampling technique. Result: The finding showed that the majority of the respondents were in the moderate category with a frequency of 103 respondents (79.2%) for fulfilling of spiritual needs. There were 105 respondents (79.2%) had a high category for quality of life. The correlation test results obtained p value <0.05 and r value = 0.348. Conclusion: There is a significant correlation between fulfillment of spiritual needs and quality of life in patient with chronic kidney failure.